2013
DOI: 10.1145/2536775
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and Identifying Missing Node Information in Social Networks

Abstract: In recent years, social networks have surged in popularity. One key aspect of social network research is identifying important missing information which is not explicitly represented in the network, or is not visible to all. To date, this line of research typically focused on finding the connections that are missing between nodes, a challenge typically termed as the Link Prediction Problem. This paper introduces the Missing Node Identification problem where missing members in the social network structure must … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 21 publications
1
42
0
Order By: Relevance
“…Our work extends Eyal et al's MISC algorithm [13]. The MISC algorithm focused on a specific variation of the missing nodes problem where the missing nodes requiring identification are "friends" of known nodes.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Our work extends Eyal et al's MISC algorithm [13]. The MISC algorithm focused on a specific variation of the missing nodes problem where the missing nodes requiring identification are "friends" of known nodes.…”
Section: Introductionmentioning
confidence: 95%
“…In this problem setting, the nodes of the network are known, and unknown links are derived from existing network information, including node information. Most recently a new missing node identification problem [13] was introduced, which locates and identifies missing nodes within the network. Previous studies have shown that combining the nodes' attributes can be effective when inferring missing links or attributes [7], [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two major research directions on the privacy and security issues in OSNs: (1) to reveal the privacy threats in OSNs by conducting surveys [16,17] and proposing attack models [26], information inference algorithms [6,8,9,13,14,19,28], de-anonymization algorithms [4,21], and re-identification algorithms [27]; and (2) to reinforce users' privacy by redesigning the OSN system structure [5,10,20,23] and conducting anonymization [22,25]. This paper investigates the privacy setting breaches, which belongs to (1).…”
Section: Related Workmentioning
confidence: 99%